ARAB STUDIES IN THE GREEK ACADEMIA: HISTORICAL CONTINUITIES, MODERN TRENDS AND CHALLENGES (Romano-arabica, 2025)
This essay intends to shed light on the historical evolution of Arab Studies in Greece from the establishment of its modern state in the 1830s until the present. More specifically, the major driving forces behind the Greek educational and academic institutions’ re-discovery of the so-called ‘‘Orient’’ are discussed, reflecting the great orientalist traditions of Europe, in addition to domestic political considerations and regional geopolitical repercussions. Taking into account the relevant academic literature written in Greek and today’s respective university departments and courses, as well as the dominant approaches towards the teaching of Islam and the culture of the Arabs, this research addresses first the historical and intellectual peculiarities of Greek Orientalism and then analyzes the factors that have affected and continue to affect the content and orientations of Arab Studies in the Greek academia between the 20th and the 21st century. The essay concludes with an assessment of the continuities with past experiences and the most recent trends regarding the status of Arab Studies.
Keywords: Greece; Graeco-Arab relations; Arab studies; Orientalism